On the possibility of justice in commercial society according to Jean-Jacques Rousseau and Adam Smith (2016)
Jean-Jacques Rousseau and Adam Smith stand on opposite sides regarding their appraisal of commercial society. The citizen of Geneva is known as one of its most harsh critiques, whereas the Scottish philosopher is considered as one of its main advocates. However, both authors coincide on one aspect: justice is the main pillar of any society. In this text, I explore this point in order to advance our understanding about the contrast between these two major figures.